Two 5S rDNA arrays in Neotropical fish species: is it a general rule for fishes ? - Martins, C.; Galetti, P. M. (Kluwer Academic Publ, 2001)
In this paper we describe Southern blot hybridization results probed with 5S rRNA genes for several Neotropical fish species representing different taxonomic groups. All the studied species showed a general trend with the 5S rDNA tandem repeats organized in two distinct size-classes. At the same time, data on 5S rDNA organization in fish genome were summarized. Previous information on the organization and evolution of 5S rRNA gene arrays in the genome of this vertebrate group are in agreement with the Southern results here presented. Sequences obtained for several fish species have revealed the occurrence of two distinct 5S rDNA classes characterized by distinct non-transcribed spacer sequences, which are clustered in different chromosomes in some species. Moreover, the 5S rDNA loci are generally distributed in an interstitial position in the chromosomes and they are usually not syntenic to the 45S rDNA. The presence of two classes of 5S rDNA in several non-related fish species suggests that this could be a common condition for the 5S rRNA gene organization in the fish genome.
Keywords: fish; non-transcribed spacer; NTS; 5S rDNA